Mediating effect of social capital in the relationship between participation and empowerment among Fadama members in Kankara Local Community, Katsina State Nigeria - Rilwanu, Aminu; Redzuan, Ma'rof; Abu Samah, Asnarulkhadi (2014)
This study has been designed empirically to find the role of social capital in the process of Fadama members’ participation and empowerment achievement. And the research tries to examine the strength of mediation through social capital toward the achievement of Fadama member’s empowerment. After the data collection; the data was analyzed by using Pearson correlation, multiple linear regression and sobel test.Findings shows that; the direct effect of participation on empowerment (ć path) is significant (b = 0.339, SE = 0.080, t = 4.208, p = 0.000). And the direct effect of participation on social capital (a path) is significant (b=0.219, SE=0.036, t=6.149, p= 0.000). Finally, the effect of social capital (MV) and outcome (b path) is significant (b=0.704, SE=0.126, t= 5.577, p=0.000). Therefore, the result depicts that participation is significantly correlated with empowerment (r=0.346, p=0.000), and also participation is significantly correlated with social capital(r=0.343, p=0.000). The partial effect of social capital on empowerment, with participation held constant, fall short of statistical significance of (β = 0.704). Moreover, the direct effect of participation on empowerment without social capital is (β = 0.238). The Sobel test shown that participation has significant effect on empowerment through social capital (z=4.115, p=0.000). From this result, the researcher concluded that there is significant effect of mediation between participation and empowerment through social capital.